(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article explores the issue of step-by-step assessment of the effectiveness of the management of higher education institutions in the areas of activity management, task management, results management on the basis of an integrated indicator in the scoring system.